Integrasi Aplikasi Dan Platform Kuis Interaktif Digital Sebagai Inovasi Pembelajaran Bahasa Arab Di Era Transformasi Teknologi Pendidikan - Wafin, Nuning Auliya'; Aliwafa, Aliwafa (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
The transformation of educational technology has driven the emergence of various innovations in language learning, including the teaching of Arabic. This study analyzes the effectiveness of integrating the Fun Easy Learn application and the Quizizz interactive quiz platform in enhancing students’ motivation, engagement, and learning outcomes in Arabic language learning at MTs. The method employed is descriptive, based on a literature review, examining various scholarly sources related to the use of interactive digital media. The findings indicate that Fun Easy Learn effectively strengthens vocabulary acquisition and basic language skills through interactive exercises, while Quizizz provides game-based assessments that are engaging and motivating for students. Students’ responses to both media were highly positive, reflected in increased participation, focus, and confidence in answering questions. The challenges identified include limited devices, unstable internet connections, and teachers’ readiness. Overall, the integration of these two digital media has the potential to improve the quality of Arabic language learning when supported by adequate infrastructure and teacher competencies.